2016
DOI: 10.1371/journal.pone.0162288
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Median Nerve Sonography as a Predictor for Short- and Long-Term Clinical Outcomes in Patients with Carpal Tunnel Syndrome: A Prospective Long-Term Follow-Up Study

Abstract: ObjectivesTo investigate the prognostic value of B-mode and Power Doppler (PD) ultrasound of the median nerve for the short- and long-term clinical outcomes of patients with carpal tunnel syndrome (CTS).MethodsProspective study of 135 patients with suspected CTS seen 3 times: at baseline, then at short-term (3 months) and long-term (15–36 months) follow-up. At baseline, the cross-sectional area (CSA) of the median nerve was measured with ultrasound at 4 levels on the forearm and wrist. PD signals were graded s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 28 publications
0
29
1
2
Order By: Relevance
“…Mondelli et al [33] showed that smaller initial CSA was predictive of better surgical outcomes. In contrast, some studies have shown that CSA was not predictive of outcomes after conservative management [34] or surgery [35]. Although our results showed smaller CSA in the good outcome group at 6 months post-injection, the difference between the groups was not significant.…”
Section: Discussioncontrasting
confidence: 99%
“…Mondelli et al [33] showed that smaller initial CSA was predictive of better surgical outcomes. In contrast, some studies have shown that CSA was not predictive of outcomes after conservative management [34] or surgery [35]. Although our results showed smaller CSA in the good outcome group at 6 months post-injection, the difference between the groups was not significant.…”
Section: Discussioncontrasting
confidence: 99%
“…Even though the current limited evidences were contradictory to ours, questioning the prognostic value of ultrasound in long-term clinical outcomes after conservative management. [22] However, the sample size in their studies was small, with no explanation for the lack of association. In spite of this, the long-term clinical efficacy after local steroid injection has been reported in a previous 2-year follow-up study.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study even questioned about the predictability of ultrasound in long-term recovery after conservative management. [22] It seemed the association between baseline ultrasound variables and long-term recovery remained ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…All studies were of a descriptive nature, most were based on crosssectional designs, although several had a prospective design. 12,13 In most cases, the upper limb was the object the study (33 articles) when compared with the lower limb (6 articles). This is mainly due to the fact that the CSA has been extensively studied.…”
Section: Characteristics Of the Selected Studiesmentioning
confidence: 99%
“…Most studies used electro diagnostic tests as the gold standard for the diagnostic confirmation of a peripheral neuropathy (after the diagnosis based on a clinical exam). 6,8,9,12,[14][15][16][17][18][19][20][21][22][23][24][25][26][27] Other studies used nuclear magnetic resonance (NMR) as the main diagnostic tool 28 or as a complementary tool, 5 which also occurred with surgical validation of findings. 4…”
Section: Characteristics Of the Selected Studiesmentioning
confidence: 99%